PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PEDIDIKAN PANCASILA DAN KEWARGANEGARAAN FKIP UNIVERSITAS RIAU - Josepta, Indra; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research of background overshadow by motivation learn seen student of social status phenomenon of old fellow economics which compose work, production and education of old fellow. This Formula research internal issue is " what is there are influence of social status significant of old fellow economics to motivation learn study program student of PPKN FKIP University of Riau". This Research aim to know influence of social status significant of old fellow economics to motivation learn study program student of PPKN FKIP University of Riau. This Research is done/conducted in study program of PPKN FKIP University of Riau in March 2016. Withdrawal of sampel at this research use technique of Simple Random Sampling that is with sampel 46 student by using quantitative descriptive data analysis by doubled linear regresi use program of SPSS 21 for Windows.For the verification of hypothesis hence to test entirety ( test F) and test of parsial to see each influence of predikator. Hence obtained result of F count/calculate smaller than F of tables of ( 1,147<2,83) there by Ho accepted Is Ha refused, its meaning do not there are influence of social status significant of old fellow economics to motivation learn student of prodi PPKN FKIP University of Riau. For the influence of work of old fellow obtained by result ( its 0,565>0,05) meaning do not significant, For the influence of production of old fellow obtained by result ( 0,144< 0,05) its meaning do not significant, For the influence of To education of old fellow obtained by result ( 0,154> 0,05) its meaning do not significant. This matter of each showing influence of predikator do not significant to motivation learn student of Prodi PPKN FKIP University of Riau. Value of R Square at this research equal to 0,076 or 7,6%. Its meaning that influence contribution by significant among/between influence of social status of old fellow economics to motivation learn student is equal to 7,6%, while 92,4% ( 100%-7,6%) influenced by other variable which do not be packed into this research.Key Words : Social Status of Economics Old Fellow, Motivation Learn Student